2005
DOI: 10.1002/ijc.20950
|View full text |Cite
|
Sign up to set email alerts
|

The role of vegetable and fruit consumption in the aetiology of squamous cell carcinoma of the oesophagus: A case‐control study in Uruguay

Abstract: There is strong evidence of a protection of high consumption of plant foods against squamous cell carcinoma of the oesophagus, but the respective role of fruits and vegetables is not well elucidated. In the time period 1996-2003, a case-control study designed in order to address this question was conducted in Uruguay. The study included 200 cases and 400 age-and sex-matched controls. High total vegetable and total fruit consumption was the strongest protective food group for this malignancy (OR 0.31, 95% CI 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…As shown in our pattern labeled as healthy, previous studies on diet and squamous cell carcinoma of the esophagus, based on individual analysis of foods and nutrients, have reported similar findings concerning the protective effect of vegetables and fruits (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The Swedish study (26) reported an inverse association with the healthy pattern, but it showed a rather small reduction in risk, which was nonsignificant.…”
Section: Discussionsupporting
confidence: 85%
“…As shown in our pattern labeled as healthy, previous studies on diet and squamous cell carcinoma of the esophagus, based on individual analysis of foods and nutrients, have reported similar findings concerning the protective effect of vegetables and fruits (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The Swedish study (26) reported an inverse association with the healthy pattern, but it showed a rather small reduction in risk, which was nonsignificant.…”
Section: Discussionsupporting
confidence: 85%
“…High consumption of fruit and vegetables has been reported to be inversely associated with incidence of sqamous cell esophageal cancer. 23,44 Therefore it has been proposed that a low calorie diet which causes low BMI is likely also to be restricted in micronutrients such as vitamins C and E, riboflavin and b-carotene, 23,45 and that these deficiencies could lead to increased risk of squamous cell carcinoma (although there is no reliable evidence that these micronutrients really are protective). Although adjusting for different dietary variables in the present study had little effect on the association, the dietary information collected at baseline was rather crude and there have been large changes in the main dietary patterns in China during recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, 52 studies fulfilled the inclusion criteria and were enrolled to this meta-analysis (Figure 1) (45,49). Two studies from Uruguay had partly overlapping study periods (52,53). Some overlap of research centers was possible in three studies from Italy or Switzerland (44,47,48), and two studies from Taiwan were partly overlapping (57, 75).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%